Option B+ Program for the Prevention of Vertical Transmission of HIV: A Case Study in Johannesburg, South Africa - Bisnauth, Melanie A.; Coovadia, Ashraf; Mbuagbaw, Lawrence; Wilson, Michael G.; Birch, Stephen (Frontiers in Public Health, 2020)
South Africa’s National Department of Health adopted WHO’s 2013 consolidated guidelines on ARVs for HIV treatment and prevention in 2015, including changes for Prevention from Mother-to-Child Transmission (PMTCT) through Option B+, aimed to reduce the HIV prevalence rate amongst women by placing them on lifelong treatment, irrespective of their CD4 count. As a result, these guidelines were implemented for the PMTCT program at Rahima Moosa Hospital. Little is known about the impact of these guidelines on the work of healthcare workers (HCWs) and no research had focused on how these changes have affected adherence for the patients. The objectives of this study is to; (1) explore the impact of the Option B+ PMTCT program on work of HCWs, and (2) understand these patient views and experiences with lifelong ART to better manage the program. Qualitative semi-structured interviews with a phenomenological approach was used. Data collection was conducted at the ANC/PNC facilities, OBGYN and Department of Pediatrics at RMMCH in Johannesburg. A qualitative approach was used with convenience sampling. Results demonstrated that work had become difficult to manage for all HCWs because of the (1) need for strengthening indicators to decrease loss-to-follow-up; (2) inconsistency in delivery of counseling & support services and; (3) lack of compassion and understanding by service providers. The difficult healthcare environment had affected overall views and experiences of these women going on lifelong ART. All patient participants (n=55) responded they chose to take the FDC pill to protect the baby’s health and believed lifelong ART could be stopped after delivery, unaware of the long-term benefits. In conclusion, the perspective of patients and HCWs in policy implementation; uptake and adherence are key indicators in informing whether the program is being adapted into healthcare facilities effectively. Extensive research needs to focus on long-term scalability and sustainability. Future evaluations need to address how interdisciplinary collaboration within healthcare facilities can improve program management.